Multicenter Experience With Mechanical Circulatory Support Using a New Diagonal Pump in 233 Children. Issue 4 (29th November 2017) - Stiller, Brigitte; Houmes, Robert Jan; Rüffer, André; Kumpf, Matthias; Müller, Andreas; Kipfmüller, Florian; Köditz, Harald; Herber Jonat, Susanne; Schmoor, Claudia; Benk, Christoph; Tibboel, Dick; Fleck, Thilo
Abstract: Technological innovations in pediatric extracorporeal life support circuits can reduce system‐related complications and may improve patients' outcome. The Deltastream DP3 (Medos Medizintechnik AG, Stolberg, Germany) is a novel rotational pump with a diagonally streamed impeller that can be used over a broad range of flows. We collected patient data from seven pediatric centers to conduct a retrospective cohort study. We examined 233 patients whose median age was 1.9 (0–201) months. The DP3 system was used for cardiopulmonary support as veno‐arterial extracorporeal membrane oxygenation (ECMO) in 162 patients. Respiratory support via veno‐venous ECMO was provided in 63 patients. The pump was used as a ventricular assist device in eight patients. Median supporting time was 5.5 (0.2–69) days and the weaning rate was 72.5%. The discharge home rate was 62% in the pulmonary group versus 55% in the cardiac group. Extracorporeal cardiopulmonary resuscitation was carried out in 24 patients (10%) with a survival to discharge of rate of 37.5%. About 106 (47%) children experienced no complications, while 33% suffered bleeding requiring blood transfusion or surgical intervention. Three patients suffered a fatal cerebral event. Renal replacement therapy was performed in 28% and pump or oxygenator exchange in 26%. Multivariable analysis identified system exchange (OR 1.94), kidney failure (OR 3.43), and complications on support (OR 2.56) as risk factors for dismal outcome. This novel diagonal pump has demonstrated its efficacy in all kinds of mechanical circulatory and respiratory support, revealing good survival rates.